Protein Phosphorylation in Human Health - Huang, Cai (InTechOpen, 2012)
15 chapters on protein phosphorylation and human health written by expert scientists. Covers most important research hot points, such as Akt, AMPK and mTOR. Bridges the basic protein phosphorylation pathways with human health and diseases. Detailed and comprehensive text with excellent figure illustration.